Energy Storage Systems - Energizing the Future: A Review - Ravi Adarsh; Rajkumar Jayakumar Kiran; Perumal Azhahia Padmanabha Pillai Thanumalaya (E3S Web of Conferences)
We are facing an energy deficit as a result of our growing energy demand [1]. In addition, with traditional energy sources depleting rapidly, solar and wind power have emerged as the primary alternatives for renewable energy. The biggest drawback of solar and wind energy sources is their irregular and intermittent nature. Energy storage systems are essential due to the growing integration of renewable energy sources into the power grid and the worsening problem of intermittency. Improving energy efficiency is viewed as a critical step toward addressing global warming and reaching the Sustainable Development Goals (SDGs). In 2020, the world’s 10 largest energy-consuming countries accounted for 66.8% of worldwide consumption, with India among them [1]. This study provides a thorough examination of several ESS topologies, encompassing their development, historical background, and present state. It also conveys system requirements and comparison based on various applications under ESS. Finally, a case study is provided in order to determine best possible ESS for EVs primarily focused in India. We have understood main parameters and criteria used to measure the importance of ESS and thus helping to choose the best option. A “performance indexing” have been performed for the specific application and a comparison is presented.